Penerapan Model Regresi Dummy Dalam Menganalisis Gender Dan Kepribadian Terhadap Kemampuan Spasial Matematis - Farizi, Reo Al; Adella, Rizqi (STAI Al-Bahjah, 2025)
This study aims to determine the application of multiple linear regression analysis using dummy variables. The use of the dummy regression model in this study uses dummy binary codes, namely 0 and 1. The use of the code to identify gender and personality variables. The gender variables in this study consisted of men and women, while personalities consisted of extroverts and introverts. The research method used in this study uses quantitative research by taking the results of the spatial ability test of SMP Negeri 2 Kapetakan students. The results showed that the use of dummy regression models could find out that gender had no influence on mathematical spatial ability and personality had an influence on mathematical spatial ability. The application of dummy regression models in analyzing gender and personality to mathematical spatial abilities can be helpful in analyzing gender and personality data cases using dummy codes. The regression equation helps in analyzing data on the influence of gender and personality on mathematical spatial ability gradually. In addition, it can know the percentage of influence generated.